Effect of twin boundary segregation on damping properties in magnesium alloy. (1st March 2017) - Somekawa, Hidetoshi; Watanabe, Hiroyuki; Basha, Dudekula Althaf; Singh, Alok; Inoue, Tadanobu
Abstract: The effect of solute segregation at deformation twin boundaries on the strength (hardness) and damping capacity was investigated using an extruded Mg-Y binary alloy. The existence of deformation twin brought about an increase in both the hardness and the damping capacity. However, a subsequent annealing had a different effect, in which segregation at twin boundaries led to a decrease in the damping capacity. This is because the segregation of yttrium stabilized the twin boundaries; as a result, these boundaries inhibited alternate shrinkage and growth of deformation twin, by which the vibration energy is absorbed. Graphical abstract: